DRD2 −141C Ins/Del Genotypes and Dopamine Profiles in Amphetamine Use Disorder - Hayder F. Al-Nassir; Adnan B. Al-Hawash; Sarmad Awad Mozan AL-Asadi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Substance use disorder arises from complex interactions between neurobiological mechanisms and genetic susceptibility, particularly within dopaminergic pathways. Specific Background: Variants in the ANKK1/DRD2 region, including the −141C Ins/Del polymorphism, have been linked to altered dopamine receptor regulation, which is central to reward processing in amphetamine use disorder (AUD). Knowledge Gap: Evidence remains limited regarding how this polymorphism relates to dopamine receptor concentrations among treated amphetamine users in Middle Eastern populations. Aims: This study examined demographic patterns of amphetamine use and evaluated the distribution of −141C Ins/Del genotypes and associated dopamine concentrations in individuals with AUD in Basra, Iraq. Results: The Ins/Ins genotype predominated among addicts, while the Ins/Del genotype was associated with markedly higher dopamine receptor concentrations compared with Ins/Ins carriers. Significant differences were observed between addicts and controls in both genotype frequencies and dopamine levels. Novelty: This work provides region-specific molecular evidence linking −141C Ins/Del heterozygosity to distinct dopaminergic profiles in AUD. Implications: The findings support the relevance of DRD2 regulatory variants in understanding neurobiological heterogeneity in amphetamine addiction and may inform future genetic screening and personalized intervention strategies. Highlights: Ins/Del genotype shows the highest dopamine receptor concentration among amphetamine users. Clear genotype distribution differences distinguish addicts from non-addicted controls. Findings add molecular evidence from an underrepresented regional population. Keywords: DRD2 −141C Ins/Del; Dopamine Receptor; Amphetamine Use Disorder; Genetic Polymorphism; Basra Population